2018
DOI: 10.7126/cumudj.389990
|View full text |Cite
|
Sign up to set email alerts
|

Dört Kavite Dezenfektan Solüsyonunun Ve İki Farklı Lazer Sisteminin Dentin Adezivlerin Mikro Makaslama Bağlanma Dayanımı Üzerine Etkinliği

Abstract: The aim of this study, was to investigate the efficacy of four cavity disinfectant solutions and two different types of laser on the micro-shear bond strength of dentin adhesives as invitro. Methods: Seventy permanent human molar teeth were sectioned parallel to the occlusal surface to expose dentin in the midcoronal. The specimens were randomly divided into seven main groups (n=10) Then cavity disinfection procedures were applied; Saline(Control); Sodium Hypochlorite (NaOCl); Chlorhexidine Gluconate (CHX); Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Post‐immersion colour changes and precipitate formation in conventional gutta‐percha points and chlorhexidine‐impregnated, active points over 21 days was also investigated 162 . One study compared the residual effects of cavity disinfection on the micro‐shear bond strength of dentine adhesive systems (self‐etch, and etch‐and‐bond) to dentine samples treated either by various cavity disinfectant solutions (RTU moderately‐acidic EOW (50 ppm), aqueous ozone (8 ppm), 2% CHX, 5.25% NaOCl) or laser application (KTP laser, Er:YAG laser) 163 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Post‐immersion colour changes and precipitate formation in conventional gutta‐percha points and chlorhexidine‐impregnated, active points over 21 days was also investigated 162 . One study compared the residual effects of cavity disinfection on the micro‐shear bond strength of dentine adhesive systems (self‐etch, and etch‐and‐bond) to dentine samples treated either by various cavity disinfectant solutions (RTU moderately‐acidic EOW (50 ppm), aqueous ozone (8 ppm), 2% CHX, 5.25% NaOCl) or laser application (KTP laser, Er:YAG laser) 163 …”
Section: Resultsmentioning
confidence: 99%
“…Fourteen reports 107,[109][110][111][112]128,[157][158][159][160][161][162][163][164] investigated the effects of EOW on dental biomaterial properties (Table 3, Table S1). One study 62 reported on the rusting of carbon steel burs immersed in different EOW solutions (acidic, moderately acidic and neutral pH) at [HOCl] >100 mg/L.…”
Section: Effects On Dental Biomaterials and Duwl Componentsmentioning
confidence: 99%
See 2 more Smart Citations